Marie Antoinette - Coppola, Sofia 1971-; Katz, Ross 1971-; Dunst, Kirsten 1982-; Faithfull, Marianne; Coogan, Steve; Davis, Judy 1956-; Schwartzman, Jason 1980-; Byrne, Rose; Weaver, Al; Henderson, Shirley 1965-; Shannon, Molly 1964-; Torn, Rip 1931-; et al. (Sony Pictures Home Entertainment, 2007)
This film is a re-telling of the turbulent life of history's favorite villainess, Marie Antoinette (Kirsten Dunst) portrays the ill-fated child princess who married France's young and indifferent King Louis XVI (Jason Schwartzman). Feeling isolated in a royal court rife with scandal and intrigue, Marie Antoinette defied both royalty and commoner by living like a rock star, which served only to seal her fate.